Information technology and sports: Looking toward Web 3.0 - Rosandich, T. J. (The Sport Journal, 2011)
From the founding of the Olympic movement in the late 19th century at the height of the Industrial Revolution through the beginning of the Information Age in the 1970s, channels of media distribution evolved from primarily written tracts in publications to electronic broadcasting. The changes in the mode of information distribution and the underlying technology over time caused the message content being promulgated to similarly change. As there were comparatively few channels available for the distribution of content during this period, a relative few individuals served as "gatekeepers" on the flow of information. These gatekeepers, such as editors and producers, exercised extraordinary control over what information entered the public domain through a process that was largely autocratic. The Information Age has changed the paradigm of information dissemination, and in so doing, has democratized the process of sharing information. The participation of the public-at-large in the development and dissemination of information that shapes humanistic ideas has grown in scale to a size unprecedented in human history. Since the advent of the Internet, this human discourse has changed over time driven both by the application of new technologies together with the exponential growth in that portion of the population that has access to them. Perhaps the most significant development in this movement was the development of the World Wide Web (the web). As the web has moved from comparatively static Web 1.0 content through the development of Web 2.0 social media applications to the beginning of Web 3.0 practices, there have been significant changes in how humans use computer technology to interact with one another. Despite the positive changes that have been brought about by the development of these technologies, such as a democratization of the information sharing process, there are still negative aspects to social media applications. There will also be significant challenges ahead in the development of new communication technologies that must be overcome before the full promise of the Internet can be realized by all.